2018
DOI: 10.1002/lary.27209
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Corticosteroids Do Not Lead to Ocular Changes: A Systematic Review and Meta‐analysis

Abstract: Use of INCS is not associated with a significant risk of elevating IOP or developing a posterior subcapsular cataract in patients with allergic rhinitis. Presence of glaucoma, however, is the real clinical adverse event of concern. There were zero reported cases of glaucoma at 12 months. Future studies should formally evaluate for glaucoma rather than use IOP measures as a surrogate. Laryngoscope, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 47 publications
0
25
0
2
Order By: Relevance
“…The most common INCS adverse effects are local, including nasal irritation, stinging and epistaxis 111 , and can usually be prevented by aiming the spray slightly away from the nasal septum. Long-term INCS use does not damage nasal mucosa or induce glaucoma 112 , and growth effects in children seem to be minimal 78 . Some INCS, such as budesonide, can be safely used during pregnancy at the recommended therapeutic dose after a thorough medical evaluation 113 .…”
Section: Box 1 | Managing Patients With Ar During the Covid-19 Pandemicmentioning
confidence: 98%
“…The most common INCS adverse effects are local, including nasal irritation, stinging and epistaxis 111 , and can usually be prevented by aiming the spray slightly away from the nasal septum. Long-term INCS use does not damage nasal mucosa or induce glaucoma 112 , and growth effects in children seem to be minimal 78 . Some INCS, such as budesonide, can be safely used during pregnancy at the recommended therapeutic dose after a thorough medical evaluation 113 .…”
Section: Box 1 | Managing Patients With Ar During the Covid-19 Pandemicmentioning
confidence: 98%
“…Case reports of increased ocular pressure from INCS have been published; 369 however, adequately powered, blinded studies have not confirmed this adverse effect. 1,370 A meta-analysis of 10 clinical trials with 2226 patients did not show a significant risk of elevating intraocular pressure or developing a posterior subcapsular cataract in patients with AR using INCS. 371 The most common side effects of INCS are local and include dryness, burning, stinging, blood tinged secretions, and epistaxis.…”
Section: Intranasal Corticosteroidsmentioning
confidence: 99%
“…1,370 A meta-analysis of 10 clinical trials with 2226 patients did not show a significant risk of elevating intraocular pressure or developing a posterior subcapsular cataract in patients with AR using INCS. 371 The most common side effects of INCS are local and include dryness, burning, stinging, blood tinged secretions, and epistaxis. The incidence of epistaxis ranges from 4% to 8% over short treatment periods (2 to 12 weeks) and can reach 20% in studies carried over a year.…”
Section: Intranasal Corticosteroidsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 No clinical relevant impact of INCS was found on intraocular pressure (IOP), glaucoma, lens opacity, nor cataract formation in recently published systematic reviews. 19,20 A meta-analysis and systematic review by Donaldson et al of 60 studies concluded that INCS are safe in the adult population. 21 High-volume irrigations.…”
Section: Delivery Devicesmentioning
confidence: 99%